Level of biochemical parameters in patients with type 2 diabetes mellitus depending on the genotype of the FokI polymorphism in the vitamin D3 receptor (VDR gene) - Konečná, Mária; Poráčová, Janka; Nagy, Melinda; Majherová, Mária; Gaľová, Jana; Gogaľová, Zuzana; Vašková, Hedviga; Mydlárová Blaščáková, Marta; Gruľová, Daniela; Sedlák, Vincent (Central European journal of public health, 2023)
OBJECTIVES: Diabetes mellitus type 2 (T2DM) is a multifactorial and polygenic disorder characterised by chronic hyperglycaemia accompanied by impaired lipid, carbohydrate, and protein metabolism. The disease is associated with several genetic polymorphisms, including the FokI polymorphism in the vitamin D receptor (VDR) gene. METHODS: We conducted a study of 327 probands (191 T2DM patients, 136 controls), with a mean age 65.06 (SD ± 10.88) years of patients with T2DM and 58.89 (SD ± 6.59) years in the healthy probands. We investigated the association between FokI polymorphism and biochemical parameters in T2DM patients in the Slovak population. Anthropometric measurements, biochemical, and genetic analysis were statistically evaluated by Statistica ver.13 software using t-tests. RESULTS: Biochemical analysis confirmed significantly higher mean values of total cholesterol (TC), triglyceride (TG), glucose (GLU), and uric acid (UA) (p < 0.001) in T2DM probands and statistically significantly lower values of high-density lipoprotein (HDL), cholesterol and vitamin D (p < 0.001). Allele frequencies and genotype distributions of the FokI (rs2228570) polymorphism were not significantly different between T2DM patients and controls (p = 0.909). Patients with T2DM and TT genotype had the highest glucose level of 11.39 (SD ± 2.32) uU/ml (p < 0.001). CONCLUSION: Our study did not provide evidence for an association of the investigated FokI polymorphism of the VDR gene with T2DM in the Slovak population. Further research is needed to evaluate the impact of single nucleotide polymorphisms (SNPs) in the VDR gene, focusing on related genetic analyses in a larger T2DM cohort.
Keywords: senioři; Genetic Predisposition to Disease; Glucose; glukosa; genotyp; jednonukleotidový polymorfismus; vitamin D receptor; HDL; lidé; Genotype; Diabetes Mellitus, Type 2; studie případů a kontrol; diabetes mellitus 2. typu; Cholesterol; cholesterol; Humans; SNP FokI; glucose; receptory kalcitriolu; genetická predispozice k nemoci; T2DM; Aged; Receptors, Calcitriol; Case-Control Studies; Polymorphism, Single Nucleotide